PECULIARITIES IN THE BEHAVIOR OF TRACE AND RARE EARTH ELEMENTS DURING GRANITIZATION AND MIGMATIZATION OF THE ELGAKAN COMPLEX (EAST SIBERIA, NYUKZHA RIVER) - Glebovitsky V.A.; Sedova I.S.; Samorukova L.M. (My University, 2006)
The behavior of major elements in the process of Neoarchean amphibolite-facies metamorphism was considered previously for occasionally pyroxene-bearing biotite–amphibole–plagioclase schists and amphibolites, which occur in the middle and lower reaches of the Nyukzha River and are identified as the Elgakan Unit. Ultrametamorphism took place in several stages. At the first stage, plagiogranite gneisses (Lc1) and rocks of an intermediate composition (sch*) were sequentially developed from the volume replacement of schists (sch).